(untitled) (The Review of Diabetic Studies, 2025)
Introduction and research problem Teamwork is essential in healthcare settings especially among nurses. Although, it’s not that easy and perhaps a challenging task to achieve effective teamwork. Effective teamwork among nurses is crucial for improving patient outcomes and enhancing the quality of care in healthcare settings. In addition, it has positive impacts on staff satisfaction and retention rates. This project aims to implement and evaluate the effectiveness of the Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS) program in improving teamwork among nurses in the female medical ward at East Jeddah Hospital in Jeddah, Saudi Arabia. Material and Method TeamSTEPPS is a training program designed to enhance teamwork and collaboration in healthcare, focusing on five key skills: team structure, leadership, situation monitoring, mutual support, and communication. This study used a quasi-experimental design to implement TeamSTEPPS-based team-building activities with 38 nurses and nursing assistants in a female medical ward, aiming to evaluate their impact on teamwork and collaboration. Summary of Results The main result shows that about three quarter of subjects’ perception improved from pre to post team structure, about (60%) of subjects perception improved from pre to post leadership, about (70%) of their perception improved from pre to post situation monitoring, more than (65%) of subjects perception improved from pre to post mutual support, more than (70%) of their perception improved from pre to post communication. Conclusion and Recommendations The study shows that a structured teamwork enhancement program improves nursing teams’ efficiency, communication, safety culture, and staff well-being. By promoting shared leadership and mutual support, healthcare organizations can reduce errors, empower nurses, and enhance patient safety, aligning with Saudi Vision 2030. Sustained leadership support, continuous learning, and ongoing evaluation are essential to maintaining and expanding these improvements.